2020
DOI: 10.1021/acs.jctc.9b01018
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Water Properties from an Efficient ab Initio Method

Abstract: Accurate prediction of the water properties from a low-cost ab-initio method still a foremost problem for chemists and physicist. Though density functional approaches starting from semilocal to hybrid functionals are tested, those are not efficiently performed for all the properties together, especially, considering energies, conformal ranking, structural and dynamics of water. Also, the inclusion of the long-range van der Waals (vdW) interaction does not improve the ordering stability of isomer. However, rely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 161 publications
0
4
0
Order By: Relevance
“…x is a quite good functional for weekly bonded systems and strongly bound solids, including the non-covalent interactions and layered materials. Other forms of the w ′ can be proposed based on the different iso-orbital indicators like α and β [32], but those may make the functional behavior quite different from F T M x , especially, for large α, which is important for non-covalent systems [54,64]. For α = 0,…”
Section: Theorymentioning
confidence: 99%
“…x is a quite good functional for weekly bonded systems and strongly bound solids, including the non-covalent interactions and layered materials. Other forms of the w ′ can be proposed based on the different iso-orbital indicators like α and β [32], but those may make the functional behavior quite different from F T M x , especially, for large α, which is important for non-covalent systems [54,64]. For α = 0,…”
Section: Theorymentioning
confidence: 99%
“…In particular, we mention that SCAN+rVV10+ U , which consists of the strongly constrained and appropriately normed (SCAN) meta-GGA combined with the rVV10 van der Waals (vdW) functional and a Hubbard U correction, has been found to perform well in case of TMOs . It is clearly admitted that the meta-GGA functionals generally perform better than the GGAs in describing solid-state properties. , Concerning MnO, it has been shown that the polymorphic structural energy difference computed using SCAN+rVV10+ U , where U is determined from linear response theory, agrees very well with that obtained from DMC values . Besides the SCAN-based methods, several other meta-GGA functionals are also proposed and tested for solid-state properties with consistently improved accuracy. , Within those recent meta-GGAs, there are the functionals constructed from the cuspless hydrogen model [(revised) meta-GGA functional from cuspless hydrogen hole ((r)­MGGAC)] , that show potential promising accuracy for different challenging problems in solid-state physics. ,, It is also quite an efficient semilocal functional that can predict band gaps of bulk and layered solids with reasonable accuracy. , …”
Section: Introductionmentioning
confidence: 99%
“…However, the accuracy of the KS DFT depends on the approximations of the exchange-correlation (xc) energy functional, which contains all of the many-electron effects beyond the Hartree approximation. Promising and yet accurate xc functionals are developed in recent times, and those are quite successful in predicting several solid-state and quantum chemical properties. ,, Despite successful implementations of semilocal approximations for solids, there are certain challenging cases for which the performance of the semilocal functional approximation is not up to the mark, even for the most advanced and promising meta-generalized gradient approximations (meta-GGA) functionals. Such a challenging solid-state problem is the stability of the polymorphs of the FeS 2 (pyrite and marcasite polymorphs) and TiO 2 (rutile and anatase polymorphs) structures.…”
Section: Introductionmentioning
confidence: 99%